2020
DOI: 10.1016/j.chemosphere.2020.127558
|View full text |Cite
|
Sign up to set email alerts
|

Efficient degradation of chloroquine drug by electro-Fenton oxidation: Effects of operating conditions and degradation mechanism

Abstract: In this work, the degradation of chloroquine (CLQ), an antiviral and antimalarial drug, using electro-Fenton oxidation was investigated. Due to the importance of hydrogen peroxide (H 2 O 2 ) generation during electro-Fenton oxidation, effects of pH, current density, molecular oxygen (O 2 ) flow rate, and anode material on H 2 O 2 generation were evaluated. H 2 O … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(52 citation statements)
references
References 76 publications
0
51
0
1
Order By: Relevance
“…The obtained results (Table 5) show an increase in the TOC removal when increasing the electrolyte concentration, reaching 93.7%TOC removal with a Na 2 SO 4 concentration of 0.3 M. Other authors have also reported the amelioration of the EF process performance when reducing the media resistance [46]. The higher amelioration, in this case, may be caused by the generation of additional oxidants following Equations ( 7) and ( 8) [47].…”
Section: Ef Treatmentmentioning
confidence: 69%
See 1 more Smart Citation
“…The obtained results (Table 5) show an increase in the TOC removal when increasing the electrolyte concentration, reaching 93.7%TOC removal with a Na 2 SO 4 concentration of 0.3 M. Other authors have also reported the amelioration of the EF process performance when reducing the media resistance [46]. The higher amelioration, in this case, may be caused by the generation of additional oxidants following Equations ( 7) and ( 8) [47].…”
Section: Ef Treatmentmentioning
confidence: 69%
“…This fact is demonstrated in Figure 3b by the increase in the dissolved TOC until the first six treatment hours, and its reduction after that, reaching a value of 70.3 mg L −1 after 24 h. Some detected aliphatic carboxylic acids were responsible for 55.8% of the remaining TOC (Figure 3b). Equations ( 7) and ( 8) [47].…”
Section: Toc Measurement and Carboxylic Acids Determinationmentioning
confidence: 99%
“…Recently, some international health organizations have allowed patients affected by Coronavirus (COVID-19) to be treated with CQ or HCQ, in an isolated manner ( Borba et al, 2020 ; Gao et al, 2020 ; Magagnoli et al, 2020 ; Tang et al, 2020 ) or combined with AZT ( Arshad et al, 2020 ; Gautret et al, 2020b ). The emergency authorization of antimalarial drugs ended up requiring large-scale manufacturing to fight the virus that ended up infecting millions of people worldwide in a few months ( Midassi et al, 2020 ) and data on the behavior and monitoring of these drugs in the environment are still very scarce.…”
Section: Resultsmentioning
confidence: 99%
“…For Midassi et al (2020) the high persistence potential of these drugs in the environment can lead to bioaccumulation and its transfer to living beings in more intensified and toxic forms, due to their antiviral and antibacterial characteristics. Coelho et al (2017) studied the stability of CQ, in which they submitted samples of the drug to degradation by acid, alkaline and neutral hydrolysis, oxidation, metal ions, heat and light and observed that CQ is susceptible to degradation only in alkaline environments and oxidation, resulting in unknown end products.…”
Section: Resultsmentioning
confidence: 99%
“… ( Bensalah et al, 2020 ) Chloroquine Electro- Fenton oxidation BDD anodes are used with the addition of FeSO 4 in the solution in order to generate a greater number of free radicals in the AOP and thus improving the cost-effectiveness, even though, the pH has to be controlled. ( Midassi et al, 2020 ) Virus Photocatalyst The photocatalyst Ag 3 PO 4 /g-C 3 N 4 synergizes the effects of Ag 3 PO 4 with those of g-C 3 N 4 achieving and improving the efficiency of the absorption of visible light; consequently, a greater destruction of the viruses by means of the ROS. ( Cheng et al, 2018 ) Ozone The is a powerful oxidant which, by generating ROS, could attack the virus in different places of its structure, especially the S-glycoprotein, inhibiting the infection process.…”
Section: Wastewater Treatment For Virus and Emerging Contaminants Removalmentioning
confidence: 99%